Smallwood Interview 09A2 - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre)
Robert Pitt continues his interview with Joseph (Joey) Smallwood begun with interview 09A. Smallwood continues briefly to talk about the people in whom he confided on political matters, such as Greg Power and Fred Rowe. audio stops at 03:20.